2010
DOI: 10.1111/j.1365-2966.2010.17357.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad-line region physical conditions along the quasar eigenvector 1 sequence

Abstract: We compare broad emission‐line profiles and estimate line ratios for all major emission lines between Lyα and Hβ in a sample of six quasars. The sources were chosen with two criteria in mind: the existence of high‐quality optical and ultraviolet spectra and the possibility of sampling the spectroscopic diversity in the 4D eigenvector 1 (4DE1) context. In the latter sense, each source occupies a region (bin) in the full width at half‐maximum (FWHM)(Hβ) versus Fe iiopt strength plane that is significantly differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
197
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(206 citation statements)
references
References 93 publications
9
197
0
Order By: Relevance
“…Separating the sample into spectral types will allow us to avoid the danger of mixing sources together that show very different spectral line profile properties. Insofar as Hβ and Feii measures reflect physical conditions in the BLR, the bins isolate sources with similar values of density, ionization parameter, and L/L Edd (see e.g., Marziani et al 2001Marziani et al , 2010. Binning allows us to also take the complexity of line profiles into account, and to separate, at least in a heuristic way, major flux contributions that are due to gas that is not likely to be virialized (i.e., the redshifted very broad component of Hβ in Pop.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separating the sample into spectral types will allow us to avoid the danger of mixing sources together that show very different spectral line profile properties. Insofar as Hβ and Feii measures reflect physical conditions in the BLR, the bins isolate sources with similar values of density, ionization parameter, and L/L Edd (see e.g., Marziani et al 2001Marziani et al , 2010. Binning allows us to also take the complexity of line profiles into account, and to separate, at least in a heuristic way, major flux contributions that are due to gas that is not likely to be virialized (i.e., the redshifted very broad component of Hβ in Pop.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Interpreting of quasar spectra in the context of a 4D parameter space stemming from eigenvector studies reveals a wide diversity of line profile properties (Sulentic et al 2000a(Sulentic et al , 2007Marziani et al 2003bMarziani et al , 2010 that are most likely driven by L/L Edd , with M BH and source orientation also playing important roles (Boroson & Green 1992;Marziani et al 2001;Yip et al 2004). The 4DE1 (4D eigenvector 1) formalism owes its Now at Instituto de Astronomía, UNAM, Ensenada Campus, Baja California, México. inception to a principal component analysis study of systematic trends in quasar spectra (Boroson & Green 1992) from the the Palomar-Green (PG) survey.…”
Section: Introductionmentioning
confidence: 99%
“…From a multi-component decomposition of the carbon line profiles (e.g. Wills et al 1985;Kuraszkiewicz et al 2002;Marziani et al 2010;Sluse et al 2011), we derived two narrow-line flux ratios B/A, which were then used to achieve a reliable macrolens-extinction solution for a standard (linear) extinction law in G. This solution allowed us to remove macrolens and extinction contributions in our quasar spectra. We note that the narrow components of the carbon lines are related to line emitting gas with typical velocities of ∼ 700 (C iii]) and 1300 (C iv) km s −1 , which belong to the inner NLER (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-component decomposition of line profiles has been used in many previous works with different aims (e.g. Wills et al 1985;Kuraszkiewicz et al 2002;Dietrich et al 2003;Sluse et al 2007;Marziani et al 2010), and recently, Sluse et al (2011) identified and studied different components of the C iii] and C iv lines in spectra of the gravitationally lensed quasar Q2237+0305.…”
Section: Microlensing In the Blermentioning
confidence: 99%
“…2.2, and each of these three emissions is most likely generated in spatially different regions (e.g., Marziani et al 2010;Sluse et al 2011;Motta et al 2012). According to Motta et al (2012), the broad wings of a given emission line could be produced in a compact region, whereas its core is probably dominated by photons arising from the NLR and the outer parts of the BLR.…”
Section: Spectroscopic Redshift Of the Main Lensing Galaxymentioning
confidence: 99%